2018
DOI: 10.18203/2394-6040.ijcmph20182596
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication practices in urban and rural areas of western India: a cross sectional study

Abstract: Background: Concerns about practice of self-medication (SM) world across are based on associated risks such as adverse reactions, disease masking, increased morbidity, wastage of resources and antibiotic resistance. SM is likely to differ between rural and urban areas of India. Systematically retrieved evidence on these differences are required in order to design targeted measures for improvement.Methods: We conducted a cross sectional study among the general population in urban (Matunga) and rural (Tala) area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
34
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 42 publications
10
34
3
Order By: Relevance
“…This finding was not in line with the findings of other studies. [ 6 18 19 20 21 22 23 27 28 34 35 37 38 39 ] Also, this study reported self-medication more prevalent in housewives and married people. This finding was similar to the study of Nair.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…This finding was not in line with the findings of other studies. [ 6 18 19 20 21 22 23 27 28 34 35 37 38 39 ] Also, this study reported self-medication more prevalent in housewives and married people. This finding was similar to the study of Nair.…”
Section: Discussionmentioning
confidence: 60%
“…[ 3 22 23 24 25 26 ] The study of Maharashtra (29.1%) and Hyderabad (30.5%) reported lower prevalence. [ 27 28 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations